2016
DOI: 10.1039/c6nj01787h
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition of alkynes to diimino Mo3S4 cubane-type clusters: a combined experimental and theoretical approach

Abstract: Newly synthesised molibdenum diimino clusters interact with alkynes leading to dithiolene species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Trinuclear precursors [Mo 3 S 4 Cl 3 (dbbpy) 3 ]X (X = Cl − , PF 6 − ; dbbpy-4,4 -di-tert-Bu-2,2 -bipyridine) [39] and [Mo 3 S 4 (acac) 3 (py) 3 ]PF 6 (acac-acetylacetonate, py-pyridine) [40] used to synthesize complexes 1, 2 and 3 as well as complex [Mo 3 {Pd(tu)}S 4 Cl 3 (dbbpy) 3 ]Cl (2) (tu-thiourea) [36], were prepared according to the published procedures. Commercially…”
Section: Methodsmentioning
confidence: 99%
“…Trinuclear precursors [Mo 3 S 4 Cl 3 (dbbpy) 3 ]X (X = Cl − , PF 6 − ; dbbpy-4,4 -di-tert-Bu-2,2 -bipyridine) [39] and [Mo 3 S 4 (acac) 3 (py) 3 ]PF 6 (acac-acetylacetonate, py-pyridine) [40] used to synthesize complexes 1, 2 and 3 as well as complex [Mo 3 {Pd(tu)}S 4 Cl 3 (dbbpy) 3 ]Cl (2) (tu-thiourea) [36], were prepared according to the published procedures. Commercially…”
Section: Methodsmentioning
confidence: 99%
“…The cluster complex [W 3 S 4 Cl 3 (dbbpy) 3 ]Cl (dbbpy = 4,4′-di-tert-butyl-2,2′-bipyridine) (Figure 1) was prepared according to the published procedure. 32 Instrumentation. Elemental analysis for C, H, N, S was carried out on a Euro EA 3000 analyzer.…”
Section: Materials Egg Phosphatidylcholine (Pc) (Avanti Polarmentioning
confidence: 99%
“…In previous works we have shown that the high lability of the thiourea ligands in easily precursor can be used to prepare tri-substituted Mo 3 S 4 complexes with 1,10-phenanthroline, 2,2'-bipyridine and its 4,4'-alkyl-substituted derivatives and N,N'-dimethylethylenediamine ligands. [54,[56][57] In this work we used this precursor for ligand-exchange reactions with phosphino-thioethers PS1, PS2 and PS3 (Figure 1 species. [57,60] Each molybdenum atom presents a distorted octahedral coordination environment, surrounded by three sulfur ligands, one chlorine, and one phosphorous and one sulfur atoms of the phosphine-thioether ligand, where all the phosphorus atoms are located trans to the capping sulfur ( 3 -S).…”
Section: Synthesis and Crystal Structurementioning
confidence: 99%
“…[54,[56][57] In this work we used this precursor for ligand-exchange reactions with phosphino-thioethers PS1, PS2 and PS3 (Figure 1 species. [57,60] Each molybdenum atom presents a distorted octahedral coordination environment, surrounded by three sulfur ligands, one chlorine, and one phosphorous and one sulfur atoms of the phosphine-thioether ligand, where all the phosphorus atoms are located trans to the capping sulfur ( 3 -S). Such preferential spatial disposition of the bifunctional ligand when coordinated to the trinuclear cluster unit is not unprecedented, and also observed in M 3 S 4 (M = Mo, W) clusters bearing aminophosphines containing P and N donor atoms.…”
Section: Synthesis and Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation